Quingwa : mga salaysay na may kasaysayan tungkol sa Plaridel, Bulacan - Veneracion, Jaime B. (Jaime Balcos); National Commission on Culture and the Arts (Philippines) (Intramuros, Manila, Philippines : National Commission for Culture and the Arts, 2013)
History of Plaridel, a town in Bulacan Province, Philippines.
Includes bibliographical references (pages 243-246) and index.
In Tagalog.
Keywords: Plaridel (Bulacan Province, Philippines) -- History